Gender Discourse in Modern University Educational Space - Yuliia Sytnykova (Educational Challenges)
Gender transformations of global social relations cause changes in various spheres of human life, in particular, the revision of traditional issues of higher education changing the modern educational space, based on the principles of humanism and equality. Therefore, the gender discourse in the university communicative space is the research purpose, it attracts the attention of scientists and it is a topical issue today. The analysis, synthesis, comparison and generalization methods as methodology are used in the paper. This study as a result dedicates to the theoretical issues of creating productive conditions for the formation of gender-loyal young people attitude to members of different sexes and get rid of their own gender stereotypes. It is argued that, future professionals will be able to learn to value their gender identity and feel free, choosing a life and career path due to the well-organized communication and awareness of student youth about their gender consciousness. Indeed, the formation of a gender-conscious personality directly depends on the rules and traditions prevailing at the university, which can be both restraining and favorable for the education of a gender-loyal person. A corporate work, a situational modeling, a processing of discussion some questions are defined as methods of this activity. The complex of these acts is an effective toolkit to solve the gender discourse issues, and the professional scientific approach of enthusiastic teachers is a driving force that helps to intensify the desired result achievement. The conclusion: we do not have to deal with gender stereotypes, we have to help youth become they want to be. Students should not pay attention to how someone identifies someone, there is no difference in abilities between the sexes, in the desire to change and create the world as they want to see it.